Menemukan Identitas Diri Siswa MA Hidayatussibyan NW Sengkerang melalui Layanan Konseling REBT - Abdul Gani (AS-SABIQUN, 2019)
This research is aimed to discover REBT consoling service to overcome the difficulty of finding out self identity for the tenth grade students of MA Hidayatussibyan NW Sengkerang in the school year 2018/2019. The type of this research is experimental research methodology which designs one-group pretest-posttest design. The population of this research is all tenth grade students of MA Hidayatussibyan NW Sengkerang, central Lombok, in the school year 2018/2019. The sample of this research is decided with proportional sample technique. The frame of the research used is one group pretest-posttest design. The data collecting technique used self identity scale. The data is analyzed by using T-test. The result of hypothesis testing indicates that T-calculation > T-table is (1.927 > 1,860) meant accepted. Therefore, it can be concluded that there is the effect of REBT consoling to overcome the difficulty of finding out self identity for the tenth grade students of MA Hidayatussibyan NW Sengkerang in the school year 2018/2019.